2019
DOI: 10.1515/helia-2018-0011
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and Path Coefficient Analysis for Morphological and Biochemical Parameters in Sunflower (Helianthus Annuus L.)

Abstract: The aim of this study was to evaluate the best performing lines in sunflower on the basis of phenotypic and genotypic correlation so that we can find out the which trait directly or indirectly effect the yield and quality of the sunflower because being an breeder our main aim is yield and quality and the lines which are performing best can be further used in the breeding programs. Sunflower is a valuable oil producing crop because it contains good quality oil composition and can be grown twice in a year. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Same trend was reported by Habibullah et al, (2007) and Sowmya et al, (2010). Plant height showed high positive indirect effect via head diameter but high negative indirect effect via days to 50 % flowering as reported by Tahir et al, (2002) and Habibullah et al, (2007).…”
Section: Path Analysissupporting
confidence: 70%
“…Same trend was reported by Habibullah et al, (2007) and Sowmya et al, (2010). Plant height showed high positive indirect effect via head diameter but high negative indirect effect via days to 50 % flowering as reported by Tahir et al, (2002) and Habibullah et al, (2007).…”
Section: Path Analysissupporting
confidence: 70%
“…Oil content is very important parameter as breeding point of view. According to Tahir et al (2019) achene oil content had positive direct effect (0.37) on achene yield per plant. Same authors concluded positive indirect effects on oil content were observed through leaf area and protein content; while plant height, internode length, leaves per plant, head diameter and 100 achene weight showed negative indirect effects; Tyagi (2011) and Chambo et al (2017) also reported same results.…”
Section: Oil Contentmentioning
confidence: 96%
“…Same authors concluded positive indirect effects on oil content were observed through leaf area and protein content; while plant height, internode length, leaves per plant, head diameter and 100 achene weight showed negative indirect effects; Tyagi (2011) and Chambo et al (2017) also reported same results. Therefore, selection of this parameter would be effective to increase the achene yield per plant by improving the seed quality (Tahir et al, 2019).…”
Section: Oil Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Other large subfamilies include Carduoideae and Cichorioideae each with more than 2000 species (Robinson 2004(Robinson , 2005. Anthemideae is the seventh largest tribe of the Asteraceae with approximately 109 genera and 1741 species worldwide grown (Tahir et al 2002). Numbers of genera and species have been gradually increasing annually.…”
mentioning
confidence: 99%